Pengembangan Media Pembelajaran Interaktif Berbasis Android pada Pembelajaran IPAS Kelas IV Sekolah Dasar - Nurhuda, Wahid Ahmad; Heri Maria Zulfiati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2024)
The use of technology provides significant benefits in learning because it can be used as a learning medium that provides meaningful learning experiences so that students can understand the correct concepts. Interactive multimedia learning media can now be developed using Android-based technology. This research aims to develop Android-based learning media on Hindu-Buddhist kingdom material for science and social subjects in class IV elementary school. The method used is research and development with a development model, namely 4-D. Validation results from experts show a feasibility level of 92% from material experts and 90% from media experts with a very feasible category. The results of the field trials showed that users felt interested and motivated to learn using media with responses given by users of 96% of students and 95% of teachers meaning that the product was very suitable for use for learning. Product effectiveness is obtained by testing the pret-test and post-test results and then calculated using the n-gain score and shows a high level of effectiveness.